Decreased dihydroartemisinin-piperaquine protection against recurrent malaria associated with Plasmodium falciparum plasmepsin 3 copy number variation in Africa - Leyre Pernaute-Lau; Mario Recker; Mamadou Tékété; Tais Nóbrega de Sousa; Aliou Traore; Bakary Fofana; Kassim Sanogo; Ulrika Morris; Juliana Inoue; Pedro E. Ferreira; Nouhoum Diallo; Jürgen Burhenne; et al. (Nature Communications)
Abstract Dihydroartemisinin-piperaquine (DHA-PPQ) is being recommended in Africa for the management of uncomplicated Plasmodium falciparum malaria and for chemoprevention strategies, based on the ability of piperaquine to delay re-infections. Although therapeutic resistance to piperaquine has been linked to increased copy number in plasmepsin-coding parasite genes (pfpm), their effect on the duration of the post-treatment prophylactic period remains unclear. Here, we retrospectively analyzed data from a randomized clinical trial, where patients received either DHA-PPQ or artesunate-amodiaquine for recurrent malaria episodes over two years. We observed an increase in the relative risk of re-infection among patients receiving DHA-PPQ compared to artesunate-amodiaquine after the first malaria season. This was driven by shorter average times to reinfection and coincided with an increased frequency of infections comprising pfpm3 multi-copy parasites. The decline in post-treatment protection of DHA-PPQ upon repeated use in a high transmission setting raises concerns for its wider use for chemopreventive strategies in Africa.